Morphology of Mandibular Condyle in The Population of Sarawak: A Retrospective Cross-sectional Study Using Digital Panoramic Radiograph - Tan , Yy Jean; Lim, Woei Tatt; Shim, Chen Kiong; Bujang, Mohamad Adam (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The morphology of the condyles changes naturally with age, gender, face type, occlusal force, functional load, malocclusion type, and the right and left sides. Although condylar shape and size differ throughout populations, there have been few investigations on condylar morphology, particularly in the Malaysian population. Methods: This retrospective, observational, cross-sectional survey was conducted at the Oral and Maxillofacial Surgery Clinic of Sarawak General Hospital from September 2021 to March 2022, involving radiographic assessment of condylar morphology from 893 panoramic radiographs. Age, gender, ethnicity and dentition status using Eichner index were extracted from the data. Descriptive statistics were used. Pearson’s chi-square test was used to determine the association between the independent variables (age, gender, ethnicity and dentition status) and the shape of the mandibular condyle. A p-value of < 0.05 was considered statistically significant. Results: Only 450 panoramic ra- diographs were included in this study. The condyles were outlined and grouped into four categories, namely pointed (40.2%), round (32.8), angled (18.8), and flat (8.2%). Condylar morphology was found to be significantly associated with gender (p<0.005) and insignificant with other independent variables. Conclusion: The findings suggest that the most prevalent condylar morphology among the Sarawak population is the pointed shape, in contrast with other previous studies that reported the round shape condylar morphology as the majority shape.